2019
DOI: 10.1016/j.dib.2019.104704
|View full text |Cite
|
Sign up to set email alerts
|

A dataset on the effect of exercise-conditioned human sera in three-dimensional breast cancer cell culture

Abstract: Epidemiological evidence shows that physical activity lowers the risk of developing breast cancer and decreases the risk of disease recurrence [1,2]. The main hypothesis on the positive effects of exercise-oncology has focused on lowering the basal systemic levels of cancer risk factors with exercise training. Recently, the effects of cancer progression control by components released after acute exercise bouts have gained attention [3,4]. However, the evaluation of the antiproliferative potential of a single e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
(7 reference statements)
0
19
0
Order By: Relevance
“…The included studies involved breast (MDA‐MB‐231, MCF‐7) (Baldelli et al., 2020; De Santi et al., 2019; Dethlefsen, Hansen, et al., 2017; Dethlefsen et al., 2016) colon (CaCo‐2, LoVo) (Devin et al., 2019), lung (A549) (Kurgan et al., 2017), and prostate (LNCaP, PC3) (Baldelli et al., 2020; Hwang et al., 2020) cancer cell lines (Table 2). Cell lines differed with respect to their mutation status of cancer critical genes including TP53, KRAS, and BRAF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies involved breast (MDA‐MB‐231, MCF‐7) (Baldelli et al., 2020; De Santi et al., 2019; Dethlefsen, Hansen, et al., 2017; Dethlefsen et al., 2016) colon (CaCo‐2, LoVo) (Devin et al., 2019), lung (A549) (Kurgan et al., 2017), and prostate (LNCaP, PC3) (Baldelli et al., 2020; Hwang et al., 2020) cancer cell lines (Table 2). Cell lines differed with respect to their mutation status of cancer critical genes including TP53, KRAS, and BRAF.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies recruited cancer survivors (Dethlefsen et al., 2016; Devin et al., 2019) whereas the other five studies recruited apparently healthy adults (Baldelli et al., 2020; De Santi et al., 2019; Dethlefsen, Hansen, et al., 2017; Hwang et al., 2020; Kurgan et al., 2017). All studies involved aerobic exercise; four studies involved high‐intensity aerobic interval exercise on a cycle ergometer, (Baldelli et al., 2020; Dethlefsen et al., 2016; Devin et al., 2019; Kurgan et al., 2017) and the remaining three studies involved continuous aerobic exercise on a cycle ergometer (Dethlefsen, Hansen, et al., 2017; Hwang et al., 2020) or treadmill (De Santi et al., 2019). One study also combined aerobic exercise with resistance training (Dethlefsen et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our in vitro results have been obtained using a ER+ breast cancer cell line (MCF7. In vitro experiments evaluating the effect of physical activity on different breast cancer cell lines have been performed by other authors using exercise-conditioned human blood serum [35]. These authors demonstrated that exercise-conditioned sera significantly reduced the ability of triple negative breast cancer cells (MDA-MB-231) to form colonies in soft agar, in comparison to pre-exercise sera collected from the same subjects.…”
Section: Discussionmentioning
confidence: 99%